MAGNETIC RESONANCE IMAGING DRUG CONTAINING DEUTERATED SARCOSINE, AND DIAGNOSTIC METHOD USING SAID DRUG - KOROL BORIS NATANOVICH; IVASHKIN PAVEL EVGENEVICH; LESIV ALEKSEI VALEREVICH; KOSENKOV ALEKSEI VIKTOROVICH; POLSHAKOV VLADIMIR IVANOVICH; KISILEVSKII MIKHAIL VALENTINOVICH (2021)
The invention relates to agents for the magnetic resonance diagnosis of oncological diseases and other diseases accompanied by a locally altered level of cellular nutrient absorption. The invention is a diagnostic drug containing at least one deuterated derivative of sarcosine, and also a diagnostic method based on the use of said diagnostic drug. The method according to the invention involves performing deuterium nuclear magnetic resonance imaging and/or deuterium nuclear magnetic resonance spectroscopy at an interval after administration of a diagnostic drug long enough for said diagnostic drug to accumulate in the region of interest of the subject's body. The proposed method makes it possible to carry out highly informative diagnoses of oncological diseases and other diseases accompanied by a locally altered level of cellular nutrient absorption. 本发明涉及用于肿瘤疾病和其他伴随着细胞营养吸收水平局部改变的疾病的磁共振诊断的试剂。本发明是含有至少一种肌氨酸氘代衍生物的诊断药物，以及基于使用该诊断药物的诊断方法。本发明的方法包括在给药后，在足以使诊断药物在受试者身体的靶区累积的时间后，采用氘核磁共振成像和/或氘磁共振光谱。所提出的方法允许对肿瘤疾病和其他伴随着细胞营养